2023
DOI: 10.1093/jeea/jvad015
|View full text |Cite
|
Sign up to set email alerts
|

The Quran and the Sword

Abstract: This paper elucidates the willingness of an autocrat to push through institutional reforms in a context where traditional authorities represented by religious clerics are averse to them and where the military control the means of repression and can potentially stage a coup. We show that although the autocrat always wants to co-opt the military, this is not necessarily true of the clerics. Exclusive co-option of the military obtains where the loyalty of the autocrat’s army is strong while the organizational str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…For example, in the case of Pakistan, Martin (2016) has observed a tendency among traditional landlords to oppose the (secular) education of their dependents lest they should seek emancipation and develop 'unrealistic expectations, and thereby cause a shortage of cheap agricultural labour (p. 87). Also, assuming a regime of autocracy, Auriol andPlatteau (2017a, 2017b) have shown that a ruler may deliberately sacrifice institutional reforms in order to placate the opposition coming from traditional leaders (including religious authorities) who resent that their erstwhile prerogatives will be encroached upon (see also Auriol et al (2021), where the army is added as a strategic actor). This raises the serious issue of how a modern state can manage the divergent interests of popular masses under the influence of traditional authorities that want to preserve the old order based on the community, on the one hand, and urban elites that have been exposed to Western values centred upon the improvement of the individual, on the other hand.…”
Section: The Political Economy Approach: Illustrating State Capture A...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the case of Pakistan, Martin (2016) has observed a tendency among traditional landlords to oppose the (secular) education of their dependents lest they should seek emancipation and develop 'unrealistic expectations, and thereby cause a shortage of cheap agricultural labour (p. 87). Also, assuming a regime of autocracy, Auriol andPlatteau (2017a, 2017b) have shown that a ruler may deliberately sacrifice institutional reforms in order to placate the opposition coming from traditional leaders (including religious authorities) who resent that their erstwhile prerogatives will be encroached upon (see also Auriol et al (2021), where the army is added as a strategic actor). This raises the serious issue of how a modern state can manage the divergent interests of popular masses under the influence of traditional authorities that want to preserve the old order based on the community, on the one hand, and urban elites that have been exposed to Western values centred upon the improvement of the individual, on the other hand.…”
Section: The Political Economy Approach: Illustrating State Capture A...mentioning
confidence: 99%
“…In reality, the political game is more complex than what has been suggested above. As theorised by Auriol, Platteau, and Verdier (2021), and explained in Chapter 1, the political game played out in countries where radical religious movements are present is a triangular game between the ruler, the military, and religious clerics. An important implication of this more complete perspective is that in order to stabilise his power and avoid a state coup, a ruler may choose to reduce the strength of the military and simultaneously co-opt religious leaders.…”
Section: B Trade-offs Between Economic Efficiency and Political Stabi...mentioning
confidence: 99%
“…All advanced economies have gone through a secular transition marked by the drastic reduction of the power and privilege of the clerical elite, the institutional importance of religion, and demands for religious sacrifice by the population (Rubin, 2017;Auriol et al, 2022). There are, however, numerous examples of failed secular revolutions in which a backlash has occurred and the religious organizations have ended up with greater political power (Auriol & Platteau, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This paper is related to several strands of literature. First, there is a growing literature in economics on co-optation of religious authorities (Rubin, 2017;Auriol & Platteau, 2017;Auriol et al, 2022). In particular, Auriol and Platteau (2017) show how secular reforms can be blocked by conservative clerics and how the risk of this occurring is greater in decentralized religions.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the Pakistani experience can therefore provide important insights for the understanding of authoritarianism in the context of electoral politics. Situating our analysis in the emerging literature on politics under authoritarianism, we argue that local government elections held by Pakistan's respective military regimes provided important instances of authoritarian power-sharing through which military rulers co-opted elites by distributing the benefits of 'joint rule' (Svolik 2012;Auriol et al 2023). More precisely, we adduce quantitative evidence to the effect that the rise of General Zia to supreme power was associated with a clear strengthening of political dynasties, and we highlight the mechanism that plausibly lies behind this relationship.…”
mentioning
confidence: 99%